ChemInform Abstract: High‐Yield Lithiation of Azobenzenes by Tin—Lithium Exchange. Issue 50 (December 2015) - Strueben, Jan; Lipfert, Matthias; Springer, Jan‐Ole; Gould, Colin A.; Gates, Paul J.; Soennichsen, Frank D.; Staubitz, Anne
Abstract: Transmetalation of Me3 Sn‐substituted azobenzenes with MeLi results in a rapid and selective Li‐Sn exchange.